(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The basis of the ideology of environmental management is the conviction that the key to creating an environmentally friendly production is the construction of an appropriate organizational structure and the distribution of responsibility for environmental protection at the appropriate levels of production management. Achieving these goals is unthinkable without the implementation of international standards of quality, environmental protection, health and safety. Achieving these goals is unthinkable without the implementation of international standards of quality, environmental protection, health and industrial safety.